The Impact of Urolithiasis in the Adaptive Response of the Organism - Dolgova, V. I. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study was to identify the impact of urolithiasis in the adaptive response of the organism. Methods: We studied 108 patients with urolithiasis including men (N1 = 51) with a mean age of 64.5 Â± 1.4 years and women (N2 = 57), with an average age of 68.2 Â± 1.7 years (P > 0.05). Three groups of methods applied. (1) Immunological and immunoassay studies (determination of cellular, humoral immunity, and phagocytic activity of peripheral blood leukocytes). Population structure of lymphoid cells was studied by immunofluorescence microscopy using monoclonal antibodies (â€œMedBioSpektr,â€ Moscow). To assess the functioning of the hypothalamic-pituitary-adrenal cortex performed quantification of cortisol in the blood serum by solid-phase enzyme immunoassay. The reagent kit â€œA-8758 Alpha Interferon - EIA-BESTâ€ and â€œA-8752 Gamma Interferon - EIA-BESTâ€ (JSC â€œVECTOR-BEST,â€ Novosibirsk) were used for quantification of interferon - alpha and IFN - gamma. (2) Methods of studying the structure of the urinary system. Radiation research for topical verification stones and renal status and upper urinary tract was performed according to the standard medical care for patients with urolithiasis (order of the Ministry of Health and Social Development of the Russian Federation, November 30, 2005, No. 704). Radionuclide indication of inflammatory lesions in the kidney scintigraphic studies performed in a planar mode gamma camera â€œCF-9200â€ (â€œGamma,â€ Hungary). (3) Methods of functional studies: To determine the adaptive capacity was used to create a computer program and the data on myocardial hemodynamic homeostasis received through tetrapolar chest rheography. Results and Discussion: The study showed that 48.7% of patients with urolithiasis had a satisfactory adaptation, 24.4% were in a state of tension of adaptive mechanisms, and 26.9% were identified a poor adaptation and failure of adaptation processes. Conclusion: It is established that the manifestation of the clinical picture of the disease provokes the formation of disintegrating types of hemodynamics and a decrease in the adaptive capacity of the organism. The course of the inflammatory process and a produced phlogogenic potential of leukocytes contributes to the development of the stress response with immune-neuroendocrine interactions.